Priming and filtering of antiherbivore defences among Nicotiana attenuata plants connected by mycorrhizal networks. (7th August 2019) - Song, Yuanyuan; Wang, Ming; Zeng, Rensen; Groten, Karin; Baldwin, Ian T.
Abstract: Arbuscular mycorrhizal fungi (AMF) establish symbiotic associations with a majority of terrestrial plants to form underground common mycorrhizal networks (CMNs) that connect neighbouring plants. Because Nicotiana attenuata plants do not respond to herbivory‐elicited volatiles from neighbours, we used this ecological model system to evaluate if CMNs function in interplant transmission of herbivory‐elicited responses. A mesocosm system was designed to establish and remove CMNs linking N. attenuata plants to examine the herbivory‐elicited metabolic and hormone responses in CMNs‐connected "receiver" plants after the elicitation of "donor" plants by wounding (W) treated with Manduca sexta larval oral secretions (OS). AMF colonization increased constitutive jasmonate (JA and JA‐Ile) levels in N. attenuata roots but did not affect well‐characterized JAs‐regulated defensive metabolites in systemic leaves. Interestingly, larger JAs bursts, and higher levels of several amino acids and particular sectors of hydroxygeranyllinalool diterpene glycoside metabolism were elevated in the leaves of W + OS‐elicited "receivers" with CMN connections with "donors" that had been W + OS‐elicited 6 hr previously. Our results demonstrate that AMF colonization alone does not enhance systemic defence responses but that sectors of systemic responses in leaves can be primed by CMNs, suggesting that CMNs can transmit and even filter defence signalling among connected plants. Abstract : Mycorrhizal colonization alone does not enhance systemic defence responses in Nicotiana attenuata plants but that sectors of systemic responses in leaves can be primed by mycorrhizal networks, suggesting that mycorrhizal networks can transmit and filter defence signalling among connected plants.